Balancing between apoptosis and survival biomarkers in the patients with tuberculous meningitis. (September 2022) - Kalita, Jayantee; Shukla, Ruchi; Pandey, Prakash C.; Misra, Usha K.
Highlights: TBM patients had higher expression of death and suppression of survival biomarkers. Caspase-3 positively correlated with TNFα, IL6 and MDA. Caspase-3 negatively correlated with XIAP, GSH and catalase. Caspase-3 expression was higher in patients with definite TBM. Patients who died had higher expression of caspase-3 and suppression of XIAP. Abstract: Background: The balancing factor of apoptosis, survival, inflammatory and oxidative stress biomarkers may determine the clinico-radiological severity and death in the patients with tuberculous meningitis (TBM). Aim: We report the relationship of death [caspase-3, malondialdehyde (MDA), tumor necrosis factor-α (TNFα), interleukin 6 (IL6)] and survival biomarkers [X-linked inhibitory apoptotic protein (XIAP), IL10, glutathione (GSH) and catalase] in TBM, and its role in determining disease severity and death. Methods: The diagnosis of TBM was based on clinical, MRI and cerebrospinal fluid (CSF) findings. Their clinical and MRI findings were noted. The severity of TBM was categorized as stages I to III. Serum and CSF caspase-3 and XIAP were measured by ELISA, and TNFα, IL6 and IL10 gene expression in peripheral blood mononuclear cells using RT-PCR (reverse-transcriptase polymerase chain reaction). Plasma MDA, GSH and catalase were measured by spectrophotometer. Results: There were 40 patients with TBM whose mean age was 31.6 years and 50% were females. TBM patients had higher expression of death (caspase-3, TNFα, IL6, and MDA) and suppression of survival biomarkers (XIAP, catalase and GSH) compared to the healthy controls. Caspase-3 positively correlated with TNFα, IL6 and MDA, and negatively with XIAP, GSH and catalase. Patients with longer duration of illness and definite TBM had higher expression of caspase-3. Patients who died has higher expression of caspase-3 and suppression of XIAP compared to those who survived. Conclusion: It can be concluded from this study that there is up-regulation of death signals and suppression of survival signals in TBM.